INFLUENCE OF STATIC ELECTRICITY ON RADON MEASUREMENT USING PASSIVE DETECTORS. Issue 3 (26th April 2019) - Chen, B; Zhao, C; Fan, D; Zhuo, W
Abstract: In order to investigate the influence of the static electricity on the measurement using passive radon detector, detectors were charged at the surface of chamber and its CR-39 elements respectively on purpose before the exposure in this study. The results of in-chamber experiments revealed that the static electricity would lead to critical influence on measurement especially when the CR-39 elements were negatively charged. The static charge would remain for several ten hours, which result in more significant influence on the short-term measurement.